Laparoscopic-assisted removal of multiple ingested magnets: An unusual and unique operative finding - Muhammad Afzal (Journal of Pediatric Surgery Case Reports, 2021)
Ingestion of two or more than two magnets is, almost never an innocent occurrence, because these are almost always associated with health morbidity, related to gastrointestinal tract complications. Children are more prone to this potentially life threatening hazard. Herein, we are presenting a unique case of three year old boy who ingested three magnetic beads one month back and presented with complaint of abdominal pain only with no other signs and symptoms. The magnetic objects were retrieved by laparoscopic assistance from gastro-colic ligament.